Interstitial lung disease in a female patient with rheumatoid arthritis - Yuliya Valeryavna Averkieva; T A Raskina; O S Malyshenko; M A Volykova; O M Maslova (Современная ревматология)
Rheumatoid arthritis (RA) is a progressive disease, resulting in joint deformation and development of severe functional disorders. Meanwhile, RA patients frequently have systemic inflammatory disorders of internal organs, which may significantly worsen quality of life, labor capacity, and be a factor determining the prognosis. Idiopathic interstitial pneumonia is of particular interest. This disease is characterized by unfavorable prognosis due to progressive fibrous rearrangement of the lung. We report a clinical case of RA with signs of interstitial lung disease.